STUDI EFISIENSI PENGELOLAAN KEUANGAN BADAN LAYANAN UMUM DAERAH (BLUD) TAMAN WISATA AIR WENDIT PERIODE 2015-2019 - Lutfia Fatmawati; Maslichah Maslichah; Afifudin Afifudin (Universitas Islam Malang, 2020)
ABSTRACT This study aims to determine the efficiency and implementation of the performance of the Financial Management Pattern of the Public Service Agency (PPK-BLU) at the Wendit Water Tourism Park. The research method used is qualitative analysis. Data collection techniques carried out by interviews, literature study, and study of documents related to research. The results of this study, based on an analysis of the implementation of the financial management patterns of the regional public service agencies (PPK-BLUD) applied in the Wendit Water Tourism Park are quite effective and efficient. This shows that in the implementation of the financial management pattern of the regional public service agencies (PPK-BLUD) in the Wendit Water Tourism Park it has been implemented well. The obstacle faced by Wendit Water Tourism Park at the planning stage is that IT applications have not been used that require a lot of time and human resources, the obstacles at the implementation stage are SDM competencies.Keywords: Performance Implementation; Public service agency; Wendit Water Park